Z badań nad obecnością skandynawów na południowym wybrzeżu Bałtyku w początkach średniowiecza - Jöns, Hauke; Kowalska, Anna B. (Slavia Antiqua. Rocznik poświęcony starożytnościom słowiańskim, 2018)
Interdisciplinary research into Scandinavian presence in the Slavic domain at the southern shore of the Baltic in the early Middle Ages has provided new data conducive to reconstruction of the natural and cultural landscapes.